ANALISIS BOUNDING ATTACHMENT SEBELUM DAN SETELAH PELAKSANAAN PIJAT BAYI - Purwanti, Sugi; Fitriyani, Tanti; Yohana, Beby (Ensiklopedia of Journal, 2024)
Baby massage is a series of massage actions performed on babies using certain techniques. Baby massage has several benefits, including: increasing the baby's body weight, increasing the baby's bond and family, increasing the baby's growth and development, increasing the baby's immune system. High bounding between parents and children stimulates optimal growth and development of children. The purpose of the study was to describe bounding attachment before baby massage. Describe bounding after baby massage. Describe the differences in bounding attachments before and after baby massage. This type of research is descriptive research with a cross sectional time approach. The population is parents who have babies under 6 months a total of 12 respondents. The study sample used a purposive sampling design. The sample size was 10 respondents. The research instrument used an infant massage checklist and a bounding questionnaire. The results of bounding research before baby massage all respondents have a sense of pride in the birth of a baby (100%), respondents take care of babies happily as much as 90%, respondents have feelings of liking for babies as much as 90%.  The result of bounding after baby massage is that all respondents have a level of attention to the baby (100%). All respondents had pride in the birth of a baby (100%). All respondents had feelings for babies (100%). All respondents had a baby's birth match with expectations (100%). The average bounding increase before and after baby massage was 2.1.Keywords : Baby Massage, Bounding Attachment